The Effects of the Alternative Electrical Generators on Air, applied on Gaza City - Al-Harazin, Hala Rezeq (Journal of natural sciences, life and applied sciences, 2023)
The study aims to identify the effect of using electricity generators as an alternative energy on the air in Gaza City, and in order to reach this end, the qualitative methodology was followed through: - Using of some data found in the official documents issued by the responsible official authorities and some parties concerned with the environment in Palestine and the Gaza Strip, and Gaza City in particular. - Reviewing research, scientific studies and published articles related to the subject of the study. - Conducting a research questionnaire on one of the target groups randomly for the purpose of serving the study. Accordingly, the study reached recent results (2023) that were not previously mentioned regarding the issue of electric generators in Gaza City and the resulting pollutants and air damage in the air surroundings of Gaza City in particular. Among the most important results obtained in my study: 1.Measuring the rate of the amount of carbon dioxide (CO2) as an air pollutant in the ambient air per generating unit, a ton unit. 2.Accordingly, the total amount of carbon dioxide (CO2) as an air pollutant emanating from power generators in the entire air surroundings of Gaza City was reached, in units of tons. 3.Measuring the average quantity of carbon dioxide pollutant per square meter of the total area of Gaza City resulting from alternative electric generators in Gaza City, unit grams per day. 4.The researcher relied on measuring the rate of the amount of carbon dioxide gas and the rate of a gram unit. The per capita share - as an Gazian citizen - of the carbon dioxide (CO2) pollutant produced by these generators was measured as a gram unit per day. 5.The researcher was able to know the value of the cumulative rate of carbon dioxide gas in the lungs of citizens in Gaza during one year, the unit kilogram. 6.Based on my results, the reality of the seriousness and catastrophe of these mentioned commercial projects appears on a daily basis, which cannot be ignored more than that, according to the consequences (healthy, environmental, and economic) that directly affected all the different aspects, and a change is still emerging; widely in all fields of society.
Keywords: electricity generators; air pollution; Gaza City; carbon dioxide (CO2); electrical deficit; environmental and healthy disaster; healthy effects; environmental effects; economic effects